Types of Expressive Speech Acts in “Isn’t it Romantic” Movie - br Sitepu, Riski Anjeli Oktavia; Afriana (IKIP Siliwangi, 2025)
Characters used expressive acts in movie to show feelings. This research analyzed expressive acts in Isn’t It Romantic. Data were from the utterances that have expressive acts. The researcher used data source Isn’t It romantic movie in this descriptive qualitative research. The research used observational method and non-participatory technique to collect data. Theory of expressive acts from Searle and Vanderveken was used to analyze data of this research. Pragmatic identity method and pragmatic competence-in equalizing was used to analyze data. The researchers found 83 data of expressive acts in the movie. 12 data from apologize, one data from deplore, 12 data from thank, nine data from greet, 26 data from complain, and 23 from compliment. The dominant was from complain because the main character, Natalie liked to complain about romantic comedy. She also became in a romantic comedy because everything weird and made she complained others and objects by expressive acts.